Pengaruh Penggunaan Model PBL Berbantuan Media Interaktif terhadap Pemahaman Konsep Matematika Materi Kesamaan Rasio pada Siswa Kelas VI SDN Oesapa Kecil 2 - Natalia Rani Letek Bedaona (Lembaga Yasin AlSys, 2026)
The low level of elementary school students’ understanding of mathematical concepts, particularly in the topic of equivalent ratios, remains a problem influenced by the use of learning methods that tend to be conventional and the limited use of interactive learning media. This condition causes students to be less active in learning, less able to relate concepts to real-life situations, and to experience difficulties in solving mathematical problems independently. This study aims to determine the effect of using the Problem Based Learning model assisted by interactive Canva media on the mathematical concept understanding of sixth-grade students at SDN Oesapa Kecil 2, as well as to identify differences in students’ concept understanding before and after the implementation of the model. This study employed a quantitative approach with a pre-experimental type through a One Group Pretest-Posttest Design. The population and sample of the study consisted of all 28 sixth-grade students, selected using the total sampling technique. The research instrument was a 20-item multiple-choice test administered during the pretest and posttest. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the paired sample t-test, and the N-Gain test with the assistance of SPSS version 23. The results showed an increase in students’ understanding of mathematical concepts after the implementation of the Problem Based Learning model assisted by Canva media, as indicated by the increase in the mean pretest score from 48.21 to 75.35 in the posttest. In addition, the results of the paired sample t-test showed a significance value of 0.000 (p < 0.05), which means that there was a significant difference between learning outcomes before and after the treatment. These findings indicate that the use of the Problem Based Learning model assisted by interactive Canva media has a significant effect on improving students’ understanding of mathematical concepts in the topic of equivalent ratios. This study affirms that the implementation of an innovative learning model combined with interactive media can be an effective alternative for improving the quality of mathematics learning, encouraging student activeness, and helping students understand concepts more deeply and contextually.